Estimation of the Young's moduli of fresh human oropharyngeal soft tissues using indentation testing. (October 2018) - Haddad, Seyyed M.H.; Dhaliwal, Sandeep S.; Rotenberg, Brian W.; Samani, Abbas; Ladak, Hanif M.
Abstract: Finite element (FE)-based biomechanical simulations of the upper airway are promising computational tools to study abnormal upper airway deformations under obstructive sleep apnea (OSA) conditions and to help guide minimally invasive surgical interventions in case of upper airway collapse. To this end, passive biomechanical properties of the upper airway tissues, especially oropharyngeal soft tissues, are indispensable. This research aimed at characterizing the linear elastic mechanical properties of the oropharyngeal soft tissues including palatine tonsil, soft palate, uvula, and tongue base. For this purpose, precise indentation experiments were conducted on freshly harvested human tissue samples accompanied by FE-based inversion schemes. To minimize the impact of the probable nonlinearities of the tested tissue samples, only the first quarter of the measured force-displacement data corresponding to the linear elastic regime was utilized in the FE-based inversion scheme to improve the accuracy of the tissue samples' Young's modulus calculations. Measured Young's moduli of the oropharyngeal soft tissues obtained in this study are presented. They include first estimates for palatine tonsil tissue samples while measured Young's moduli of other upper airway tissues were obtained for the first time using fresh human tissue samples. Graphical abstract: fx1 Highlights: Indentation testing of fresh oropharyngeal tissues harvested from patients undergoing surgery for obstructive sleep apnea. Inverse finite-element modeling was performed to estimate the Young's modulus of each tissue. Young's moduli for the palatine tonsils, soft palate, uvula and tongue base were estimated.